2014
DOI: 10.1111/jre.12161
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the menstrual cycle on inflammatory cytokines in the periodontium

Abstract: This study indicated that changes occurring during the menstrual cycle influence the periodontium and induce inflammatory conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 40 publications
1
35
0
Order By: Relevance
“…These physiological changes all have a major impact on the entire body, including the oral ecosystem. Increased levels of sex hormones in serum have direct physical consequences in the oral cavity: individuals experience gingivitis due to an enhanced inflammatory response to plaque while the actual plaque levels are not increased [Güncü et al, 2005;Kinane et al, 2006;Khosravisamani et al, 2014]. The exact mechanism for this phenomenon is unclear, but the presence of sex hormone receptors on the surface of gingival cells, osteoblasts and periodontal ligament fibroblasts suggests that changes in the concentrations of sex hormones have a direct effect on oral mucosa and periodontium [Khosravisamani et al, 2014].…”
Section: Puberty As An Example Of Allostasismentioning
confidence: 99%
See 1 more Smart Citation
“…These physiological changes all have a major impact on the entire body, including the oral ecosystem. Increased levels of sex hormones in serum have direct physical consequences in the oral cavity: individuals experience gingivitis due to an enhanced inflammatory response to plaque while the actual plaque levels are not increased [Güncü et al, 2005;Kinane et al, 2006;Khosravisamani et al, 2014]. The exact mechanism for this phenomenon is unclear, but the presence of sex hormone receptors on the surface of gingival cells, osteoblasts and periodontal ligament fibroblasts suggests that changes in the concentrations of sex hormones have a direct effect on oral mucosa and periodontium [Khosravisamani et al, 2014].…”
Section: Puberty As An Example Of Allostasismentioning
confidence: 99%
“…Increased levels of sex hormones in serum have direct physical consequences in the oral cavity: individuals experience gingivitis due to an enhanced inflammatory response to plaque while the actual plaque levels are not increased [Güncü et al, 2005;Kinane et al, 2006;Khosravisamani et al, 2014]. The exact mechanism for this phenomenon is unclear, but the presence of sex hormone receptors on the surface of gingival cells, osteoblasts and periodontal ligament fibroblasts suggests that changes in the concentrations of sex hormones have a direct effect on oral mucosa and periodontium [Khosravisamani et al, 2014]. Furthermore, the hormone estradiol, found in serum in boys and girls during puberty [Kumar, 2013], has been suggested to act as growth factor for selected oral bacteria: Prevotella intermedia can accumulate estradiol as a substitute for vitamin K in vitro [Kornman and Loesche, 1982].…”
Section: Puberty As An Example Of Allostasismentioning
confidence: 99%
“…Previous literature has also reported that sex steroid hormones affect periodontal tissues, saliva, oral mucosa wound healing, periodontal disease progression and bone turnover (Khosravisamani et al., ; Mascarenhas, Gapski, Al‐Shammari, & Wang, ; Mascarenhas et al., ). However, the mechanism underlying the association between periodontal status and menstrual cycle has not been fully elucidated.…”
Section: Introductionmentioning
confidence: 97%
“…Changes in serum oestradiol and progesterone levels during the menstrual cycle may affect locally released cytokines (Baser et al., ; Becerik et al., ; Khosravisamani et al., ; Markou, Boura, Tsalikis, Deligianidis, & Konstantinidis, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation